2013
DOI: 10.1186/1743-422x-10-86
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the transduction efficiency of five adeno associated virus serotypes and VSV-G pseudotype lentiviral vector in lung cancer cells

Abstract: BackgroundLung cancer is the leading cause of cancer-related deaths in the US. Recombinant vectors based on adeno-associated virus (AAV) and lentivirus are promising delivery tools for gene therapy due to low toxicity and long term expression. The efficiency of the gene delivery system is one of the most important factors directly related to the success of gene therapy.MethodsWe infected SCLC cell lines, SHP-77, DMS 53, NCI-H82, NCI-H69, NCI-H727, NCI-H1155, and NSCLC cell lines, NCI-H23, NCI-H661, and NCI-H46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“… 30 , 31 So far, only a few studies have demonstrated in vivo gene editing following LV delivery of Cas9. 31 , 32 , 33 , 34 In this study, we chose LV as the delivery tool and suggested a better therapeutic efficacy over the renewal cycle of the epidermis. Then, the disrupted cytoskeletal integrity, abnormal differentiation, and irregular proliferation were ameliorated.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 So far, only a few studies have demonstrated in vivo gene editing following LV delivery of Cas9. 31 , 32 , 33 , 34 In this study, we chose LV as the delivery tool and suggested a better therapeutic efficacy over the renewal cycle of the epidermis. Then, the disrupted cytoskeletal integrity, abnormal differentiation, and irregular proliferation were ameliorated.…”
Section: Discussionmentioning
confidence: 99%
“…To date, AAV serotype 2 (AAV2) is the most commonly used AAV vector already used in clinical trials. Tumor cell in vitro transduction with different AAV serotypes of a variety of human cells has been reported, but there is still much controversy with reference to the transduction efficiency of AAV vectors in human malignant cells [38][39][40]. However, there are certain problems associated with viral vectors for cancer gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Genes chosen for delivery are diverse and have shown different results; the myogenic regulation involving myostatin and follistatin genes has been extensively studied. There is a tendency to use the AAV [17], and it is emerging as one of the most popular gene delivery systems because of a lack of pathogenicity in humans, mild immune response, and its long-term and efficient transgene expression in various cells [18]. Some AAVs do not integrate into the cell genome and can exist long term in non-dividing cells.…”
Section: Gene Therapymentioning
confidence: 99%